EVALUASI CITRA KERUSAKAN PADA PANEL DISTRIBUSI LISTRIK TEGANGAN RENDAH BERDASARKAN TERMOGRAFI INFRAMERAH - slamet wahyudi; andi asni b; aswadul fitri Saiful Rahman (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2019)
The change of electrical energy into heat energy in faults of low voltage electrical distribution panels causes an increase in temperature, this is what makes thermography using an infrared camera become one effective method for detecting it, but it is often found misinterpretation when the thermal image generated from the infrared camera is processed more further and lead to wrong in decision making regarding actions to be taken next.Through this research, the method of operating and taking thermal images using infrared cameras is introduced in accordance with the correct standard operating procedures, so that it is expected when applying standard operating procedures in the field and good validation techniques will minimize the misinterpretation that has an impact on decisions and corrective actions.